Generic pattern recognition models based on EEG-MI brain computer interfaces for wheelchair steering control - Al-Qaysi, Ziadoon Tareq AbdulWahhab (Tanjong Malim, 2020)
Generic pattern recognition models based on EEG-MI brain computer interfaces for wheelchair steering control by Al-Qaysi, Ziadoon Tareq AbdulWahhab